Β-Ga2O3:Ce as a fast scintillator: An unclear role of cerium. (February 2019) - Drozdowski, Winicjusz; Makowski, Michał; Witkowski, Marcin E.; Wojtowicz, Andrzej J.; Galazka, Zbigniew; Irmscher, Klaus; Schewski, Robert
Abstract: β-Ga2 O3 and β-Ga2 O3 :Ce crystals have been grown by the Czochralski method and their scintillation properties have been studied by means of pulse height, radioluminescence and scintillation time profile measurements. It is shown that although the scintillation of β-Ga2 O3 :Ce is related to intrinsic excitonic emission, the doping with Ce improves some characteristics of the material. The prominent samples of β-Ga2 O3 :Ce display fast 6 ns (40%) scintillation, with total light yields of about 5000 ph/MeV. Highlights: β-Ga2 O3 and β-Ga2 O3 :Ce crystals have been grown by the Czochralski method. Semiconducting samples (pure and Ce-doped) scintillate with yields of ∼5000 ph/MeV. Doping with Ce improves some properties of β-Ga2 O3 .